Effective managerial performance and education: towards closing the gaps. (9th February 2009) - Yasin, Mahmoud M.; Gomes, Carlos F.; Almeida, Filipe
Desired performance-related characteristics for entry-level managers are studied from the perspective of 106 Portuguese executives. The results indicate that soft characteristics and skills, such us leadership, entrepreneurship and organisational learning skills, appear to be more important than technical skills. While these skills and characteristics are valued by today's business organisations, the educational system does not appear to be preparing its graduates accordingly. The resulting educational gaps have important performance-related implications to both the business organisations and the higher education institutions.